Children's active play: self-reported motivators, barriers and facilitators - Rowan Brockman; Russell Jago; Kenneth R Fox (BMC, 2011)
Physical activity has important benefits for children's physical health and mental wellbeing, but many children do not meet recommended levels. Research suggests that active play has the potential to make a valuable contribution to children's overall physical activity, whilst providing additional cognitive, social and emotional benefits. However, relatively little is known about the determinants of UK children's active play. Understanding these factors provides the critical first step in developing interventions to increase children's active play, and therefore overall physical activity. Eleven focus groups were conducted with 77, 10-11 year old children from four primary schools in Bristol, UK. Focus groups examined: (i) factors which motivate children to take part in active play; (ii) factors which limit children's active play and (iii) factors which facilitate children's active play. All focus groups were audio-taped and transcribed verbatim. Data were analysed using a thematic approach. Children were motivated to engage in active play because they perceived it to be enjoyable, to prevent boredom, to have physical and mental health benefits and to provide freedom from adult control, rules and structure. However, children's active play was constrained by a number of factors, including rainy weather and fear of groups of teenagers in their play spaces. Some features of the physical environment facilitated children's active play, including the presence of green spaces and cul-de-sacs in the neighbourhood. Additionally, children's use of mobile phones when playing away from home was reported to help to alleviate parents' safety fears, and therefore assist children's active play. Children express a range of motivational and environmental factors that constrain and facilitate their active play. Consideration of these factors should improve effectiveness of interventions designed to increase active play.